Geometrija Foucaultovega nihala - Saksida, Grega (Matrika, 2020)
The article examines the rotation of the swing plane of the Foucault pendulum. It employs only elementary mathematics and physics. It relates the angle of rotation of the plane to the geometry of the Earth's gravitational field, which is in the approximation of a perfect sphere an equipotential surface of the field. The magnitude of the rotation is expressed as a function of geographical latitude of the pendulum and length of the observation period. Finally, using the Gauss-Bonnet theorem of differential geometry, the results are briefly generalised to equipotential surfaces of arbitrary fields space.
Keywords: ekvipotencialna ploskev; equipotential surface; Foucault pendulum; Foucaultovo nihalo; Gauss-Bonettov izrek; Gauss-Bonnet theorem; nihajna ravnina; swing plane